Chart stalking, list making, and physicians' efforts to track patients' outcomes after transitioning responsibility. Issue 4 (30th January 2018) - Bowen, Judith L; O'Brien, Bridget C; Ilgen, Jonathan S; Irby, David M; ten Cate, Olle
Abstract : Context: Transitions of patient care responsibility occur frequently between physicians. Resultant discontinuities make it difficult for physicians to observe clinical outcomes. Little is known about what physicians do to overcome the practical challenges to learning these discontinuities create. This study explored physicians' activities in practice as they sought follow‐up information about patients. Methods: Using a constructivist grounded theory approach, semi‐structured interviews with 18 internal medicine hospitalist and resident physicians at a single tertiary care academic medical center explored participants' strategies when deliberately conducting follow‐up after they transitioned responsibility for patients to other physicians. Following open coding, the authors used activity theory (AT) to explore interactions among the social, cultural and material influences related to follow‐up. Results: The authors identified three themes related to follow‐up: (i) keeping lists to track patients, (ii) learning to create tracking systems and (iii) conducting follow‐up. Analysis of participants' follow‐up processes as an activity system highlighted key tensions in the system and participants' work adaptations. Tension within functionality of electronic health records for keeping lists (tools) to find information about patients' outcomes (object) resulted in using paper lists as workarounds. Tension between paper lists (tools) and protecting patients' health information (rules) led to rule‐breaking or abandoning activities of locating information. Finding time to conduct desired follow‐up produced tension between this and other activity systems. Conclusion: In clinical environments characterised by discontinuity, lists of patients served as tools for guiding patient care follow‐up. The authors offer four recommendations to address the tensions identified through AT: (i) optimise electronic health record tracking systems to eliminate the need for paper lists; (ii) support physicians' skill development in developing and maintaining tracking systems for follow‐up; (iii) dedicate time in physicians' work schedules for conducting follow‐up; and (iv) engage physicians and patients in determining guidelines for longitudinal tracking that optimise physicians' learning and respect patients' privacy. Abstract : The authors describe physicians' strategies for tracking transitioned patients and illuminate tensions related to list functionality, workplace rules, and finding time for learning about patients' outcomes.